Population aging: opportunity for business expansion, an invitational paper presented at the Asia-Pacific Economic Cooperation (APEC) International Workshop on Adaptation to Population Aging Issues, July 17, 2017, Ha Noi, Viet Nam - Mary Beth Arensberg (BMC, 2018)
Abstract A longer life brings opportunities for older adults and their families as well as for their communities. Commercial businesses can be successful in innovating on these opportunities and achieving business expansion when they better understand the market dynamics and spectrum of older adults as consumers and view them more as assets rather than as burdens to society. While there is no "typical" older adult consumer, some traits, characteristics, and physical realities may be more common, including those related to family and community, the shopping experience, brand marketing and packaging, food and nutrition, and health. The opportunities of longer life are impacted by health and underscore the importance of positive, healthy aging-related behaviors like good nutrition and active lifestyles. Healthy aging also requires a sustained commitment and action from country leaders to formulate evidence-based polices--like systematic nutrition screening and intervention-and healthcare workforce training and education that can strengthen and support an active aging population. In addition, governments should consider engaging commercial businesses to help set sustainable policies that can advance products for older adults. Finally, governments should set national and local goals to incentivize commercial business development and investment in public-private partnerships to improve quality of care, promote healthy aging, and impact outcomes for noncommunicable diseases, ultimately benefitting population health for Asia-Pacific Economic Cooperation (APEC) countries.